Evaluation of dietary protein and lipid requirements of two-banded seabream (Diplodus vulgaris) cultured in a recirculating aquaculture system - Acar, Ümit; Kesbiç, Osman Sabri; Ergün, Sebahattin; Güroy, Derya; Yiğit, Murat; Yılmaz, Sevdan; Karga, Mustafa; Gültepe, Nejdet; Bulut, Musa (Springer Science and Business Media LLC, 2013)
The objective of this study is to investigate the effects of dietary protein and lipid levels on the growth performance and bioeconomic benefits of two-banded seabream (Diplodus vulgaris) juveniles, a candidate species for aquaculture sector. Eight experimental diets were formulated with four protein (50, 45, 40 and 35 %) levels for each of the two lipid levels (15 and 10 %). Triplicate groups of juvenile fish with an average initial body weight of ~3.64 g were reared in a recirculating aquaculture system and hand fed twice a day until satiation for a period of 60 days. In the experiment, no difference in survival rate was found between the different groups. Relative growth rate (RGR), specific growth rate (SGR), feed conversion ratio (FCR) and daily feed intake were not significantly affected by increasing protein and/or lipid treatments in this present study. However, the RGR, SGR and FCR values showed slightly better efficiency in the experimental group (35/15) fed with lower protein content (35 %) and higher lipid level (15 %) compared with those fed other diets. According to bioeconomic analyses results, the diet with the 35 % protein and 15 % lipid generated the best profit. The results suggest that two-banded seabream can be accepted as a promising alternative species for the aquaculture industry and optimum growth of two-banded seabream fingerlings can be obtained when they are fed a diet containing 35 % crude protein and 15 % crude lipid.
Keywords: 14. Life underwater; 6. Clean water